Food Malayan Berhad's Intention to Grow Its Businesses. (June 2016) - Tan, Albert; Mitra, Sumit
This case concerns and discusses how a company can shape its growth strategy, given the current competitive environment and increasing operating costs. The case will help students to realize the important of aligning its business objectives with its operations. The food industry is facing declining profit margins due to fierce competition internally and also from overseas competitors. It is, therefore, important to align its strategies with its operations to grow its revenue while reducing its operating costs.